1998
DOI: 10.1177/000348949810701005
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Glottic Stenosis: A Canine Model

Abstract: Posterior glottic stenosis is a disabling disease in which the vocal folds are fixed near the midline. This allows adequate vocal fold adduction for voicing, but does not permit useful abduction for ventilation. The most common cause is prolonged endotracheal intubation for mechanical ventilation, and the incidence is estimated at 4% for intubations between 5 and 10 days. Currently, our understanding and treatment modalities are based on retrospective reviews of small, nonrandomized clinical experiences. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The endotracheal tube (ETT) places pressure at the posterior commissure as it bends in a caudal direction in the around the tongue base to allow the distal end to sit coaxial within the proximal trachea, positioning helped by the balloon cuff (4). In PGS, this pressure results in mucosal ulceration, prolonged inflammation, granulation tissue, and fibrosis that ultimately contracts the arytenoids and often extends into the cricoarytenoid joint (Figure 1) (4, 6, 89). Bogdasarian proposed a classification system with an interarytenoid scar band with posterior sinus tract (Class I), limited motion of arytenoids (Class II), fixation of one cricoarytenoid joint (Class III), and ultimately fixation of both cricoarytenoid joints (Class IV) however, this classification system has not been assessed to be predictive of therapy or outcomes (2).…”
Section: Introductionmentioning
confidence: 99%
“…The endotracheal tube (ETT) places pressure at the posterior commissure as it bends in a caudal direction in the around the tongue base to allow the distal end to sit coaxial within the proximal trachea, positioning helped by the balloon cuff (4). In PGS, this pressure results in mucosal ulceration, prolonged inflammation, granulation tissue, and fibrosis that ultimately contracts the arytenoids and often extends into the cricoarytenoid joint (Figure 1) (4, 6, 89). Bogdasarian proposed a classification system with an interarytenoid scar band with posterior sinus tract (Class I), limited motion of arytenoids (Class II), fixation of one cricoarytenoid joint (Class III), and ultimately fixation of both cricoarytenoid joints (Class IV) however, this classification system has not been assessed to be predictive of therapy or outcomes (2).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4]13 Outcomes of LTS with associated inflammatory changes and granulation tissue are known to improve with local surgical therapy. [2][3][4]13 Outcomes of LTS with associated inflammatory changes and granulation tissue are known to improve with local surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in order to study the interventions to laryngeal stenosis, a series of animal models have been previously established. In 1998, Msrk S. et al [8] reported a New Zealand rabbit model, which developed posterior glottic stenosis by injury of CO 2 laser ablating laryngeal tissues in different depths. In addition, in the study conducted by Cláudia Schweiger [9], with the use of the New Zealand rabbit model, it was observed that the subglottic stenosis was caused by intubation, nylon brush and Bugbee cautery, in which most animals survived at two weeks after injury for further observation of laryngotracheal stenosis.…”
Section: Introductionmentioning
confidence: 99%